The case-control method design and applications (New York ; Oxford : Oxford University Press, 2009)
This title helps readers address a number of general and specific questions dealing with the case-control and other case-based methods, including questions of how to design and implement a case-control study that minimizes biases, how to analyze the data to appropriately deal with confounding variables and more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Case-control method